MONITORING VOLTAGE AND TEMPERATURE PARAMETERS AT SMARTPHONE SOLAR CHARGER STATIONS USING GOOGLE SPREADSHEET - Fakhrudin, Muhamad; Jamaaluddin (Journal for Technology and Science, 2025)
Objective: Consumption of electronic devices, particularly smartphones, is on the rise, leading to a significant reliance on electrical energy by humans. However, the battery of your smartphone may deplete rapidly with daily usage from morning till night. To cater to individuals with high mobility and outdoor tendencies, a charging station has been developed. Method: This station utilizes two sensors, namely PZEM-004T and DHT 22, which are then processed by the NodeMCU ESP 8266. The NodeMCU ESP 8266 generates temperature, current, and voltage readings, which are displayed on a 20x4 LCD screen and transmitted via Google Spreadsheet. Results: The sensor data accuracy is impressive, with the DHT 22 sensor achieving 98.2% and the PZEM 004T sensor reaching 94.5%. Based on the test results, it can be concluded that this tool effectively facilitates monitoring during the operation of solar panels. Novelty: To cater to individuals with high mobility and outdoor tendencies, a charging station has been developed.